Kendala Pengembangan Pariwisata di Destinasi Pariwisata Labuan Bajo Nusa Tenggara Timur - Antonius Sugiarto; I Gusti Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2020)
Labuan Bajo is wellknown tourism destination to foreign countries. The uniqueness of Labuan Bajo is in the natural panorama and marine tourism. This makes Labuan Bajo become a super priority destination of Indonesia's tourism development. Tourism development includes attractions, accessibility, amenities, and ancillary. Labuan Bajo is still faced with contraints regarding the development of the four components of tourism products, so that the tourism potential has not been optimally developed. The purpose of this study is to find out the tourism potential in Labuan Bajo, and contraints in the development of four components products. The data analysis technique used is qualitative descriptive. The Data collected by interview, observation, and documentation study methods are interpreted to obtain a comprehensive analysis. The results of the study show that many tourism potential that can be developed into a tourist attraction. All of this potential is supported by good amenities and branding of Labuan Bajo as a world class tourism destination. But there are fundamental problems in the development of tourism in Labuan Bajo. These problems are human resources that are not qualified in shaping tourist attraction, geographical conditions that require a lot of costs in developing accessibility, spatial planning that has not supported the development of amenities, and mismatches between the central government and local government in tourism development. Keywords: Development, Potential, Problems, Tourism